Analisis Perkembangan Jaringan Bisnis dalam Upaya Strategi Kompetitif Kedai Susu Wayang Windu di Tangan Generasi Sandwich - Pebrianti, Syifa Nurazizah; Putri, Andini Febriani; Pertiwi, Asri Banyu; Hasanah, Rindy Cahyani; Riansyah, Muhamad; Marselina, Resya Dwi (Melati Institute, 2023)
This research is a field study with descriptive qualitative methods. The data collection techniques used were interviews, observation and documentation. While data analysis is done through data reduction, presentation, and conclusion drawing. The results of this study indicate that KS Wayang Windu's business network in the hands of the Sandwich Generation has developed very well. There is more room for product marketing and more business networks that can cooperate with KS Wayang Windu. The strategy implemented by KS Wayang Windu has proven to be effective, as it has made a strong business strategy in marketing their products throughout the West Java region. When viewed from the overall business network, KS Wayang Windu has a huge potential to succeed in the food and beverage industry.